Latex-Infused Porcine Abdominal Model: A Novel Microsurgery Simulator for Deep Inferior Epigastric Perforator Dissection - Shaffrey, Ellen C.; Zeng, Weifeng; Nicksic, Peter J.; Eftekari, Sahand C.; Frank, Jennifer M.; Dingle, Aaron M.; Poore, Samuel O. (Journal of Reconstructive Microsurgery, 2023)
Background Perforator dissection and flap elevation are routinely performed for microsurgical reconstruction; however, there is a steep learning curve to mastering these technical skills. Though live porcine models have been utilized as a microsurgical training model, there are significant drawbacks that limit their use, including cost, limited ability for repetition, and obstacles associated with animal care. Here we describe the creation of a novel perforator dissection model using latex augmented non-living porcine abdominal walls. We provide anatomic measurements that demonstrate valuable similarities and differences to human anatomy to maximize microsurgical trainee practice.Methods Six latex-infused porcine abdomens were dissected based on the deep cranial epigastric artery (DCEA). Dissection was centered over the abdominal wall mid-segment between the second and fourth nipple line. Dissection steps included exposure of lateral and medial row perforators, incision of anterior rectus sheath with perforator dissection, and dissection of DCEA pedicle. DCEA pedicle and perforator measurements were compared with deep inferior epigastric artery (DIEA) data in the literature.Results An average of seven perforators were consistently identified within each flap. Assembly of the model was performed quickly and allowed for two training sessions per specimen. Porcine abdominal walls demonstrate similar DCEA pedicle (2.6 ± 0.21 mm) and perforator (1.0 ± 0.18 mm) size compared with a human's DIEA (2.7 ± 0.27 mm, 1.1 ± 0.85 mm).Conclusion The latex-infused porcine abdominal model is a novel, realistic simulation for perforator dissection practice for microsurgical trainees. Impact on resident comfort and confidence within a microsurgical training course is forthcoming.
Keywords: resident education; microsurgery; surgical simulation